Moderating role of leader-member exchange between the relationship of organizational justice and organizational citizenship behavior - Muhammad Irfan Sheeraz; Ungku Norulkamar Ungku Ahmad; Muhammad Ishtiaq Ishaq; Khalil Md. Nor (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
Extensive research has examined the relationship between organizational justice and organizational citizenship behavior, with mixed results. Most of these studies have used self-reported measuring instruments, and several have used dyadic data to avoid common methodological biases. This study sought to determine the relative impact of organizational justice dimensions on the organizational citizenship behavior of individuals (OCBI) and the organizational citizenship behavior of organizations (OCBO). It uses a double dyad method (faculty member-colleague and faculty member-supervisor), involving data from 151 faculty groups working in private higher education institutions of Pakistan. The data was analyzed using moderated regression analysis through AMOS software. The results revealed that distributive justice and procedural justice are related to altruism, courtesy, and civic virtues, while interactional justice is only correlated with courtesy. Additionally, leader-member exchange (LMX) was found to be a significant moderator in the relationship between organizational justice and organizational citizenship behavior.
Keywords: 330; organizational justice; distributive justice; procedural justice; interactional justice; organizational citizenship behavior; leader-member exchange (LMX); higher education institutions; universities